Analisis Interaksi Senyawa Sinularin dan Turunannya terhadap Reseptor pada Kanker Payudara dengan Metode Penambatan Molekul: Analysis of the Interaction of Sinularin Compounds and Their Derivatives with Receptors in Breast Cancer by Molecular Docking Method - Bismar Al Bara; Indah Laily Hilmi; Hadi Sudarjat (Bachelor of Pharmacy Study Program, Faculty of Health Sciences, Universitas Singaperbangsa Karawang, 2024)
Over the past three decades, there have been thousands of women undergoing treatment with tamoxifen. But there is a decrease or even no response to the breast cancer chemotherapy treatment. This phenomenon can occur due to resistance. sinularin has potential as a cancer drug.This study aims to evaluate the interaction of sinularin compounds and its derivatives with breast cancer receptors such as estrogen receptor alpha with PDB code: 5W9C, progesterone receptor with PDB code: 1A28, and human epidermal growth factor receptor 2 using proteins with PDB code: 3PP0 using molecular docking methods to determine anticancer potential.This research method is in-silico research. The research was conducted by screening test compounds such as prediction of compound potential using PASS Online Server, prediction of physicochemical properties using SwissADME, and prediction of compound toxicity using ProTox 3.0. Then validation of the method using AutoDock Vina, Next molecular docking using AutoDock Vina, and visualization of molecular docking results using Biovia Discovery Studio Visualizer. The results showed that sinularin compounds and their derivatives showed anticancer potential through the PASS test, low toxicity, and compliance with the Lipinski Rule of Five. Method validation showed RMSD values ​​below 2.0 Å. In molecular docking, sinularin showed a binding affinity value with a value of -8.027 kcal/mol which was better than tamoxifen with a value of -7.61 kcal/mol, although still below the native ligand of estrogen receptor alpha with a value of -8.815 kcal/mol. Sinularin and its derivatives have potential as anticancer agents through interaction with ERα and HER-2. Keywords: Breast Cancer; Sinularin; Molecular Docking.